2017
DOI: 10.1007/s12035-017-0451-4
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of Cellular Prion Protein in α-Synuclein Transport in Neurons

Abstract: The cellular prion protein, encoded by the gene Prnp, has been reported to be a receptor of β-amyloid. Their interaction is mandatory for neurotoxic effects of β-amyloid oligomers. In this study, we aimed to explore whether the cellular prion protein participates in the spreading of α-synuclein. Results demonstrate that Prnp expression is not mandatory for α-synuclein spreading. However, although the pathological spreading of α-synuclein can take place in the absence of Prnp, α-synuclein expanded faster in PrP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 70 publications
5
72
0
Order By: Relevance
“…A number of reports claim that the role of the cellular prion protein in neurodegeneration is not limited to prion disorders, but extends also to the pathogenesis of Alzheimer's disease and synucleinopathies (16,17,20,23,36). Indeed, several reports indicate that PrP C mediates the neurotoxicity of several protein aggregates (a-synuclein, amyloid b) in two different ways.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports claim that the role of the cellular prion protein in neurodegeneration is not limited to prion disorders, but extends also to the pathogenesis of Alzheimer's disease and synucleinopathies (16,17,20,23,36). Indeed, several reports indicate that PrP C mediates the neurotoxicity of several protein aggregates (a-synuclein, amyloid b) in two different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the spreading of αSyn can occur in the absence of PrP C , suggesting it is not required for the transport of αSyn. However, this transport is faster in the presence of PrP C …”
Section: Prpc As a Mediator Of The Spreading Of αSynmentioning
confidence: 96%
“…More recently, PrP C was identified as a possible sensor for αSyn aggregates . In addition to interacting with αSyn and amyloid‐β (Aβ), it was recently proposed that PrP C might act as a conformation‐specific sensor for disease‐associated proteins, suggesting a more general role in the pathogenesis of various neurodegenerative diseases .…”
Section: Different Cell Surface Proteins Mediate the Internalization mentioning
confidence: 99%
“…Indeed, recombinant -synuclein fibrils spread among neurons in wild-type mice (Luk et al, 2012;Masuda-Suzukake et al, 2014;Urrea et al, 2017). Intranigral or intrastriatal inoculation of PD-derived LB extracts in monkeys results in progressive nigrostriatal neurodegeneration (Recasens et al, 2014).…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…From these results, several laboratories started to analyse whether PrP C might also be a cellular partner of other PS (Resenberger et al, 2011a), and whether PrP C may participate in or regulate the spreading of particular misfolded aggregates and associated neuropathologies. Recent results suggest that membrane-anchored PrP C may also bind to -synuclein (Aulic et al, 2017;Ferreira et al, 2017;Urrea et al, 2017) and may participate in its neuronal spreading (Aulic et al, 2017;Urrea et al, 2017). In this review, we discuss neuronal cell surface molecules with high affinity for disease-associated PS, particularly -amyloid and -synuclein, with a focus on the role of PrP C in this process.…”
Section: Introductionmentioning
confidence: 99%